Direct withdrawal of a knife lodged in the thoracic spinal canal in a patient with normal neurologic examination: is it safe? - (:unkn) unknown (My University, 2016)
Stab wound injuries to the spinal cord are rare, although they commonly cause complete or incomplete neurological deficits. Normal neurological examination with a knife traversing the spinal canal is extremely rare. Here we report on a patient with a knife lodged in the thoracic spine with normal neurological examination and describe direct withdrawal of the knife with excellent results that have not been reported to date. A 50-year-old male patient was admitted to the emergency service because of his sustaining a stab wound to thoracic 3-4 level due to a knife traversing the spinal canal and still lodged in the vertebral bodies. His neurological examination was normal. The knife was withdrawn in the operating room under general anesthesia without bleeding or cerebrospinal fluid leakage. After withdrawal neurological examination was normal and control magnetic resonance imaging showed no abnormalities. Surgical exploration is suggested for spinal stab wounds if there is a retained body. Some authors recommend exploration even no foreign body is detected. Incomplete or complete cord injuries deserve surgical exploration, but in a patient with normal neurological examination direct withdrawal can be a safe option. Exploration of the wound surgically may have risks associated with enlarging the incision, muscle dissection, enlarging dural tear and bony removal, which may have long-term adverse effects. The operation team must be ready for urgent exploration. Cerebrospinal fluid leakage, excessive bleeding or any neurological deficit after removal must mandate surgical exploration. Long-term close follow-up of the patient has paramount importance for late complications such as infection and pseudomeningocele development.
Keywords: Neurological disorders; Trauma